Visual skills in elite athletes - Wimshurst, Z. L. (2012)
In order to perform at the highest level, athletes will acquire information from all of their sensory systems. It would be intuitive to assume that the most vital information for the majority of sports-related tasks will be gathered via the visual system and that this visual input tends to override information from other sensory sources. Researchis beginning to highlight the links between the ability to quickly and accurately pick up visual information and quality of performance in a range of sports (Erickson, 2007). The purpose of this thesis is to investigate the visual skills of elite athletes and the effect of these visual skills on performance at the highest level of sport. The first experimental chapter aims to assessth e current level of visual skills presenti n athleteso f the highest level and compare these to lower level athletes, as well as by gender and sport. The thesis then goes on to develop a tool to use in order to assess the visual demand so far particular sport. In Chapters Four and Five visual training programmes are used with the aim of improving visual skills of elite athletes. In one study improvements are measured by playing position and the next applies different methods of vision training and improvements are measured not only in visual skill but also in sport-specific skill. Finally Chapter Six uses fvIRI to compare the different brain function of expert athlete with novices. This thesis has shown that athletes from different sports, genders and abilities show assorted visual skills. It has also developed a tool to uncover which visual skills an expert considers most important for their sport. The training studies have proved successful in improving not only the visual skills of elite athletes but also their sport specific skills. Finally, it has been shown that experts use different areas of their brain when making sporting judgements, regardless of whether the decisionis in the sport in which they excel or in an unfamiliar sport.